2019
DOI: 10.1016/j.aninu.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of xylanase and protease on growth performance, digesta viscosity, nutrient digestibility, immune and oxidative stress status, and gut health of newly weaned pigs

Abstract: This study was to investigate the effect of dietary supplementation with xylanase and protease on growth performance, digesta viscosity, apparent ileal digestibility (AID) of nutrients, and gut health in nursery pigs. Forty-eight pigs (24 barrows and 24 gilts at 21 d of age with 7.2 ± 0.4 kg BW) were randomly allotted to 4 dietary treatments (2 × 2 factorial arrangement) in a randomized complete block design and fed in 2 phases (phase 1 for 10 d and phase 2 for 14 d). Factors were xylanase (0 or 45,000 XU/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(133 citation statements)
references
References 59 publications
(97 reference statements)
6
110
2
Order By: Relevance
“…Although the jejunal digesta viscosity was not affected by either factors in this study, the viscosity can be affected by the ingredient in the diet (19,31) and the ratio of insoluble to soluble NSP (68). The viscosity observed in this study ranged from 1.8 to 1.9 mPa•s, which is lower than previously reported by Duarte et al (10) and Passos et al (14) due to differences in dietary compositions.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Although the jejunal digesta viscosity was not affected by either factors in this study, the viscosity can be affected by the ingredient in the diet (19,31) and the ratio of insoluble to soluble NSP (68). The viscosity observed in this study ranged from 1.8 to 1.9 mPa•s, which is lower than previously reported by Duarte et al (10) and Passos et al (14) due to differences in dietary compositions.…”
Section: Discussioncontrasting
confidence: 72%
“…In phase 1 (d 0-10), the ETEC challenge tended to reduce (P = 0.092) the ADG, whereas the use of synbiotics increased (P < 0.05) it, regardless of the challenge. In phase 2 (d [10][11][12][13][14][15][16][17][18][19][20] and overall, the ADG was reduced (P < 0.05) when pigs were challenged with ETEC, whereas it was not affected by the use of synbiotics. The ADFI was not affected by the use of synbiotics during the pre-challenge period (d 0-7).…”
Section: Growth Performancementioning
confidence: 97%
See 1 more Smart Citation
“…Oxidative stress is directly linked with inflammation since oxidants are activators of the nuclear transcription factor NF-kB, the critical regulator of inflammation [28]. Previous studies have reported reduced oxidative stress and inflammation level in the weaning pig fed corn-SBM based diet by supplementation of NSP-degrading enzymes, such as xylanase and β-mannanase [29,30]. However, our result showed that the β-mannanase supplementation did not affect the concentrations of AGP and HP (APP parameters) as well as SOD and GPx (oxidative stress parameters; Figure 1).…”
Section: Serum Oxidative Stress and Immune Parametersmentioning
confidence: 99%
“…Furthermore, in recent years, the role of xylanase has extended beyond its original intent due to reports of unexpected health benefits, particularly reductions in mortality in grow-finish pig production ( Zier-Rush et al, 2016 ). There have also been reports of improvements in gut barrier integrity ( Tiwari et al, 2018 ) and reductions in markers of oxidative stress ( Duarte et al, 2019 ) in nursery pigs supplemented with xylanase, but there is a dearth of literature in the grow-finish pig. Therefore, the experimental objective was to investigate the impact of xylanase on energy bioavailability, oxidative status, and gut function and morphology of growing pigs fed a diet higher in insoluble fiber and given a longer adaptation time than typically reported.…”
Section: Introductionmentioning
confidence: 99%